2022
DOI: 10.3390/medicina58050677
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy Provides Limited Therapeutic Effects on Carpal Tunnel Syndrome: A Systematic Review and Meta-Analysis

Abstract: Night wrist splinting has been a conservative treatment for carpal tunnel syndrome. The addition of extracorporeal shock wave therapy provides an alternative treatment. However, strong evidence on the clinical effectiveness of extracorporeal shock wave therapy for carpal tunnel syndrome is still lacking. This study aimed to investigate the effectiveness and safety of extracorporeal shock wave therapy compared with treatments of night wrist splints alone for patients with carpal tunnel syndrome. In this systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Both interventions were reported to have similar effects in terms of improving pain, function and electrophysiological nerve parameters [91]. Another meta-analysis of seven clinical trials (376 patients) reported that adding shock wave therapy to a conservative treatment intervention such as a nocturnal wrist splint produced a transient improvement in pain and functional benefit for only four weeks [92].…”
Section: Role Of Eswt In Carpal Tunnel Syndromementioning
confidence: 99%
“…Both interventions were reported to have similar effects in terms of improving pain, function and electrophysiological nerve parameters [91]. Another meta-analysis of seven clinical trials (376 patients) reported that adding shock wave therapy to a conservative treatment intervention such as a nocturnal wrist splint produced a transient improvement in pain and functional benefit for only four weeks [92].…”
Section: Role Of Eswt In Carpal Tunnel Syndromementioning
confidence: 99%
“…Therefore, kinesio taping appears to be a valid and recommended intervention complementary to other therapies to obtain greater effectiveness rather than a stand‐alone therapy in patients with CTS. Some of these conventional therapies comprise neurodynamic techniques for decreasing pain and functionality (de Arenas‐Arroyo et al., 2021), shock waves for functionality (with contradictory outcomes for pain at present) (Chen et al., 2022; Xie et al., 2020), the use of splints to improve functionality, severity, and the neurophysiological aspects studied in this pathology (Karjalainen et al., 2023). Therefore, the combination of techniques within a conventional treatment plan appears to be a valid approach to address all the clinical signs of this pathology whose beneficial effects have been shown to be only slightly inferior to those of surgical treatment (Shi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, kinesio taping appears to be a valid and recommended intervention complementary to other therapies to obtain greater effectiveness rather than a stand-alone therapy in patients with CTS. Some of these conventional therapies comprise neurodynamic techniques for decreasing pain and functionality (de Arenas-Arroyo et al, 2021), shock waves for functionality (with contradictory outcomes for pain at present) (Chen et al, 2022;Xie et al, 2020), the use of splints to improve functionality, severity, and the neurophysiological aspects studied in this pathology (Karjalainen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack in the literature of follow-up after ESWT treatments over the 6-month time [ 25 , 25 ]. In a recent systematic review and meta-analysis on ESWT [ 26 , 26 ] in carpal tunnel syndrome, on 376 patients, ESWT did not show superior efficacy compared to treatment with night wrist splint alone at 2 and 3 months follow-up. The effect of LCI in treating mild to moderate carpal tunnel syndrome is evident.…”
Section: Discussionmentioning
confidence: 99%